Gender and Social Norms Assessment GENSoNA: A tool in the CGIAR Gender Transformative Research Methodologies (GTRM) toolkit - Farnworth, Catherine Rozel; Rietveld, Anne (2025)
Tool 4 in the Gender Transformative Research Methodologies Toolkit. The GENSoNA Tool is a preliminary tool to help guide gender-transformative engagements in a selected community. It generates locally specific detail on how gender and social norms are expressed in a community/village or at the level of a group of stakeholders/organization. This information can be used by external researchers and project partners to deepen their understanding of the community or the group/organization. The same information helps to build awareness among the target community/group of the gender and social norms that guide their attitudes, expectations and aspirations. They are then able to assess what they have learned and to act upon their analyses. Main focus on communities. Tool is available in English and Spanish.